Assessing Quality of Life Among Patients with Diabetes Mellitus, Hypertension or Both Diseases in Al-Najaf Province /Iraq - ali shlash abd alhamza al ibrahimy; Haydar F.Al-Tukmagi (College of Pharmacy University of Baghdad, 2017)
this study deals with effect of diabetes and hypertension on quality of life